Global Synthesis of Air-Sea CO2 Transfer Velocity Estimates From Ship-Based Eddy Covariance Measurements - Yang, Mingxi; Bell, Thomas G.; Bidlot, Jean-Raymond; Blomquist, Byron W.; Butterworth, Brian J.; Dong, Yuanxu; Fairall, Christopher W.; Landwehr, Sebastian; Marandino, Christa A.; Miller, Scott D.; Saltzman, Eric S.; Zavarsky, Alexander (Frontiers in Marine Science, 2022)
The air-sea gas transfer velocity (K660) is typically assessed as a function of the 10-m neutral wind speed (U10n), but there remains substantial uncertainty in this relationship. Here K660 of CO2 derived with the eddy covariance (EC) technique from eight datasets (11 research cruises) are reevaluated with consistent consideration of solubility and Schmidt number and inclusion of the ocean cool skin effect. K660 shows an approximately linear dependence with the friction velocity (u*) in moderate winds, with an overall relative standard deviation (relative standard error) of about 20% (7%). The largest relative uncertainty in K660 occurs at low wind speeds, while the largest absolute uncertainty in K660 occurs at high wind speeds. There is an apparent regional variation in the steepness of the K660-u* relationships: North Atlantic ≥ Southern Ocean > other regions (Arctic, Tropics). Accounting for sea state helps to collapse some of this regional variability in K660 using the wave Reynolds number in very large seas and the mean squared slope of the waves in small to moderate seas. The grand average of EC-derived K660 (-1.47 + 76.67u* + 20.48u*2 or 0.36 + 1.203U10n + 0.167U10n2) is similar at moderate to high winds to widely used dual tracer-based K660 parameterizations, but consistently exceeds the dual tracer estimate in low winds, possibly in part due to the chemical enhancement in air-sea CO2 exchange. Combining the grand average of EC-derived K660 with the global distribution of wind speed yields a global average transfer velocity that is comparable with the global radiocarbon (14C) disequilibrium, but is 20% higher than what is implied by dual tracer parametrizations. This analysis suggests that CO2 fluxes computed using a U10n2 dependence with zero intercept (e.g., dual tracer) are likely underestimates at relatively low wind speeds.